A Retrospective Study: The Profile of New Patient with Vitiligo - Nurina Dhani Rahmayanti; Rahmadewi Rahmadewi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Vitiligo occurs worldwide, with prevalence of 0.1 to 2.0 percent, commonly begins in childhood or young adulthood, with peak onset of 10 to 30 years, but it may occur at any age. Based on vitiligo new patient profile, treatment and recovery of patients could be expected to be better. Purpose: To evaluate the profile of new patients with vitiligo. Methods: A restrospective descriptive study was carried out in Medical Cosmetic Division Dermatovenereology Outpatient Clinic Soetomo Hospital Surabaya in 2012-2014. Result: New patient of vitiligo in Medical Cosmetic Division Dermatology and Venereology Out Patient Clinic Soetomo Hospital Surabaya in 2012-2014 were 188, which was 0.2% of total patient. The most frequent age was 25-44 years old as much as 61 patients, and mostly woman (68.1%).  Fourty three point one percent came to out patient clinic after having vitiligo for more than 12 months. 78.5% had multiple lesions and 83.5% with lesion less than 10 cm2. Topical corticosteroid were given to 86.2%, sun block in 84%, topical oksoralen in 48.9% and cosmetic camouflage in 10.6% patient. Most of them (69.5%) never came to out patient clinic to check their disease. Conclusion: The average of vitiligo case in Soetomo Hospital Surabaya is 62 patient per year and mostly woman Key words: vitiligo, retrospective, profile.